Strategi Card Sort dapat Meningkatkan Hasil Belajar Matematika Sekolah Dasar - Jannah, Miftahul; Anna Fauziah; Supriyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the mathematics learning outcomes of first grade students of SD Negeri 45 Lubuklinggau State Elementary School after the of the Card Sort Learning. The research method uses a pre-experimental design method with a one group pretest-posttest research design. The sampling technique uses a random sampling technique. The data collection technique uses a test. The test instrument used is in the form of an essay totaling 8 questions. Data were analyzed using the t-test. Based on the results of the t-test analysis, it was obtained 5,3870) ≥ (1.729) so Ha is accepted and Ho is rejected. Thus, it can be concluded that the Implementation of the Card Sort Strategy on the Mathematics Learning Outcomes of Grade I Students of SD Negeri 45 Lubuklinggau significantly reaches the KKTP. Keywords: Card sort, Learning outcomes, Mathematics, Strategy